First look at humpback whale (Megaptera novaeangliae) song structure from western South Africa. Issue 3 (2nd July 2020) - Hawkey, James Seymour; Elwen, Simon Harvey; James, Bridget Susan; Prinsloo, Alexa Simone; Gridley, Tess
Abstract : Humpback whales are known for their complex and well-structured song that is typically produced on low-latitude breeding grounds. However, there is increasing evidence of song production on migration routes and high-latitude feeding grounds. Within a breeding ground and season, males share songs that progressively change over time. Song production on migration routes leads to the cultural transmission and sharing of songs. This is the first assessment of song structure in humpback whales recorded near Cape Town, South Africa. Song was identified in recordings made between 9 September 2016 and 21 October 2016 on a moored hydrophone located in Fish Hoek, False Bay. Thirty-nine song sessions were recorded, consisting of nine distinct units, forming ten themes. Themes occasionally overlapped in time, indicating multiple simultaneous singers. They were repeated on multiple days with consistent patterns in theme transition, demonstrating song sharing amongst individuals. Convergence on a similar song structure suggests singing whales originate from the same breeding stock. We propose that an unknown proportion of these whales continue to sing beyond the recognised breeding season. These data support previous studies that found that singing is not restricted to low-latitude breeding sites.